Bad factoring

by ChatGPT

This page presents a transcript of a ChatGPT session from Fall of 2023. I asked it write a couple of proofs involing limits, which then led me to ask it to focus on factoring polynomials.

It was not particularly good at these kinds of questions at that point in time, when it was using GPT v3.

You said:
write a proof of the fact that lim_{eps -> 1) (x^2-1)/(x-1) = 2
ChatGPT said:
ChatGPT

To evaluate limx1x21x1\lim_{x \to 1} \frac{x^2 - 1}{x - 1}, we can use algebraic simplification:

First, factor the numerator:

x21x^2 - 1 is a difference of squares which can be factored as (x+1)(x1)(x + 1)(x - 1).

So, x21x1=(x+1)(x1)x1\frac{x^2 - 1}{x - 1} = \frac{(x + 1)(x - 1)}{x - 1}

Now, as long as x1x \neq 1, we can cancel out x1x - 1 from the numerator and the denominator, resulting in:

x+1x + 1

Now, evaluate the limit as xx approaches 1:

limx1(x+1)=1+1=2\lim_{x \to 1} (x + 1) = 1 + 1 = 2

Therefore, limx1x21x1=2\lim_{x \to 1} \frac{x^2 - 1}{x - 1} = 2.

You said:
write an epsilon-delta proof of the fact that lim_{eps -> 1) (x^2-1)/(x-1) = 2
ChatGPT said:
ChatGPT

Alright, let's construct an ϵ\epsilon-δ\delta proof for the given limit:

Claim: limx1x21x1=2\lim_{x \to 1} \frac{x^2 - 1}{x - 1} = 2

Proof: Given ϵ>0\epsilon > 0, we want to find a δ>0\delta > 0 such that if 0<x1<δ0 < |x - 1| < \delta, then x21x12<ϵ\left|\frac{x^2 - 1}{x - 1} - 2\right| < \epsilon.

Start with the expression:

x21x12\left|\frac{x^2 - 1}{x - 1} - 2\right|

=x212x+2x1= \left| \frac{x^2 - 1 - 2x + 2}{x - 1} \right|

=x22x+1x1= \left| \frac{x^2 - 2x + 1}{x - 1} \right|

=x1= |x - 1|

We want this to be less than ϵ\epsilon. So:

x1<ϵ|x - 1| < \epsilon

But this is just the condition that 0<x1<δ0 < |x - 1| < \delta.

Thus, we can choose δ=ϵ\delta = \epsilon.

In conclusion, for any ϵ>0\epsilon > 0, if 0<x1<ϵ0 < |x - 1| < \epsilon, then x21x12<ϵ\left|\frac{x^2 - 1}{x - 1} - 2\right| < \epsilon. This completes the ϵ\epsilon-δ\delta proof of the given limit.

You said:
factor $x^4 - 2*x^3 - 2*x^2 + 7*x - 6$
ChatGPT said:
ChatGPT

To factor the polynomial x42x32x2+7x6x^4 - 2x^3 - 2x^2 + 7x - 6, we can start by looking for potential rational roots using the Rational Root Theorem. This theorem tells us that any rational root, when written in its lowest terms p/qp/q, will have pp as a factor of the constant term (6 in this case) and qq as a factor of the leading coefficient (1 in this case).

From this, our potential rational roots are: ±1, ±2, ±3, ±6.

We can start by testing each of these roots using synthetic division or polynomial evaluation.

f(1)=142(13)2(12)+7(1)6=0f(1) = 1^4 - 2(1^3) - 2(1^2) + 7(1) - 6 = 0

So, x=1x = 1 is a root.

Next, we can use synthetic division or polynomial long division to divide x42x32x2+7x6x^4 - 2x^3 - 2x^2 + 7x - 6 by x1x - 1.

Performing the division, we get:

x3x23x+6x^3 - x^2 - 3x + 6

Now, we look for factors of this cubic polynomial.

By trial, we see: f(1)=13123(1)+6=3f(1) = 1^3 - 1^2 - 3(1) + 6 = 3, so x=1x = 1 is not a root of the cubic polynomial. f(2)=23223(2)+6=0f(2) = 2^3 - 2^2 - 3(2) + 6 = 0, so x=2x = 2 is a root.

Now, divide x3x23x+6x^3 - x^2 - 3x + 6 by x2x - 2:

Performing the division, we get:

x2+x3x^2 + x - 3

This quadratic can be factored further as: x2+x3=(x+3)(x1)x^2 + x - 3 = (x + 3)(x - 1)

So, our original polynomial can be factored as:

x42x32x2+7x6=(x1)(x2)(x+3)(x1)x^4 - 2x^3 - 2x^2 + 7x - 6 = (x - 1)(x - 2)(x + 3)(x - 1)

This is the complete factorization of the polynomial in question.

You said:
that's not right!
ChatGPT said:
ChatGPT

I apologize for the oversight in the previous calculation. Let's try factoring the polynomial x42x32x2+7x6x^4 - 2x^3 - 2x^2 + 7x - 6 again.

The Rational Root Theorem gives potential rational roots as: ±1, ±2, ±3, ±6. Let's use synthetic division or polynomial evaluation to test each of these potential roots.

By evaluating at x=1x = 1: f(1)=142(13)2(12)+7(1)6=0f(1) = 1^4 - 2(1^3) - 2(1^2) + 7(1) - 6 = 0 So, x=1x = 1 is a root.

Using synthetic division or polynomial long division to divide x42x32x2+7x6x^4 - 2x^3 - 2x^2 + 7x - 6 by x1x - 1, we get:

x3x23x+6x^3 - x^2 - 3x + 6

Now we'll again look for roots of this cubic polynomial.

By evaluating f(2)f(2), we get: f(2)=23223(2)+6=846+6=4f(2) = 2^3 - 2^2 - 3(2) + 6 = 8 - 4 - 6 + 6 = 4 So, x=2x = 2 is not a root of the cubic polynomial.

Trying other potential roots and applying synthetic division might help further break down the polynomial, but without a calculator to check each value, it can be tedious. However, one might also employ techniques like graphing or computer software to aid in finding these roots.

For now, based on the previously derived information, we know that:

x42x32x2+7x6=(x1)(x3x23x+6)x^4 - 2x^3 - 2x^2 + 7x - 6 = (x - 1)(x^3 - x^2 - 3x + 6)

We can attempt to factor the cubic further or break it down using other algebraic techniques.

You said:
But x=1 is *not* a root. You're making a simply arithmetic error there.
ChatGPT said:
ChatGPT

I apologize for the oversight. Let's correct this mistake and attempt to factor the polynomial x42x32x2+7x6x^4 - 2x^3 - 2x^2 + 7x - 6 once again.

Starting again with the polynomial, let's evaluate for some of the potential rational roots:

For x=1x = 1: f(1)=142(13)2(12)+7(1)6=122+76=2f(1) = 1^4 - 2(1^3) - 2(1^2) + 7(1) - 6 = 1 - 2 - 2 + 7 - 6 = -2

You're right; x=1x = 1 is not a root.

Let's try x=2x = 2: f(2)=242(23)2(22)+7(2)6=16168+146=0f(2) = 2^4 - 2(2^3) - 2(2^2) + 7(2) - 6 = 16 - 16 - 8 + 14 - 6 = 0

So x=2x = 2 is indeed a root.

Using synthetic division or polynomial long division to divide x42x32x2+7x6x^4 - 2x^3 - 2x^2 + 7x - 6 by x2x - 2, we get:

x3+0x24x3x^3 + 0x^2 - 4x - 3

This is now our cubic polynomial. We can continue the same process to find the roots of this polynomial.

By evaluating the cubic polynomial at x=1x = 1: f(1)=13+04(1)3=143=6f(1) = 1^3 + 0 - 4(1) - 3 = 1 - 4 - 3 = -6

So, x=1x = 1 is also not a root of the cubic polynomial.

Next, let's look at potential factorizations. Given that polynomial factoring can be complex, and without the aid of graphing or other computational tools, breaking down the cubic might be more challenging.

From our previous steps, we know:

x42x32x2+7x6=(x2)(x34x3)x^4 - 2x^3 - 2x^2 + 7x - 6 = (x - 2)(x^3 - 4x - 3)

Without further computational aid, this might be the furthest we can break down the polynomial without additional insights or steps.